Complete bipartite Ramsey numbers - Hasmawati; Assiyatun H.; Baskoro E.T.; Salman A.N.M. (Utilitas Mathematica, 2009)
It is known that R(K1,p, K2,m) ≤ 2p - 2 + m for p ≥ 3 and m ≥ 2. In this paper, we show that the Ramsey numbers R(K 1,5, K2,5) = 13 and R(K1,5, K2,6) = 13 . Furthermore, we show that if k is any natural number, then R(K 1,5, K2,m) = m + 8 for m=-2 + 4 (Equation presented).